2016
DOI: 10.3390/ijerph13030341
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Air Pollution on Hospital Emergency Room Visits for Respiratory Diseases: Urban-Suburban Differences in Eastern China

Abstract: A study on the relationships between ambient air pollutants (PM2.5, SO2 and NO2) and hospital emergency room visits (ERVs) for respiratory diseases from 2013 to 2014 was performed in both urban and suburban areas of Jinan, a heavily air-polluted city in Eastern China. This research was analyzed using generalized additive models (GAM) with Poisson regression, which controls for long-time trends, the “day of the week” effect and meteorological parameters. An increase of 10 μg/m3 in PM2.5, SO2 and NO2 corresponde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 53 publications
6
18
0
Order By: Relevance
“…Number of patients' visits increased with the increase of concentration levels. Similar results have been obtained in some other research studies [12,13].…”
Section: Discussionsupporting
confidence: 92%
“…Number of patients' visits increased with the increase of concentration levels. Similar results have been obtained in some other research studies [12,13].…”
Section: Discussionsupporting
confidence: 92%
“…NO 2 is associated with asthma visits 21,[23][24][25]29,33 , COPD 22,33,34 , URTI 22 , pneumonia 29 , as well as all respiratory ED visits 35,36 . Samoli et al found signifi cant association of NO 2 with total, cardiovascular and respiratory mortality 31 .…”
Section: Discussionmentioning
confidence: 99%
“…(2) The partial autocorrelation function (PACF) was applied to select the degree of freedom of time according to the minimum absolute values of the sum of PACF for lags up to 30 [ 19 , 20 ]. Degrees of freedom for temperature and relative humidity were defined based on previous studies [ 9 , 21 ]. (3) Indicators for the weekends (DOW) and the public holidays (holiday) were adjusted as dummy variables in the model [ 6 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…(3) Indicators for the weekends (DOW) and the public holidays (holiday) were adjusted as dummy variables in the model [ 6 , 19 ]. (4) The naturally smooth functions of two variables, average temperature and relative humidity, were included into the model to control the confounding effects of meteorological factors on the association between air pollution and respiratory disease hospitalization [ 21 ]. According to previous studies, the effect of temperature on health had a lag effect of more than 10 days [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%